Total phenols, antioxidant potential and antimicrobial activity of walnut (Juglans regia L.) green husks - Oliveira, Ivo (2008)
The total phenols content and antioxidant and antimicrobial activities were studied in walnut (Juglans regia L.) green husks aqueous extracts of five different cultivars (Franquette, Mayette, Marbot, Mellanaise and Parisienne). Total phenols content was determined by colorimetric assay and their amount ranged from 32.61 mg/g of GAE (cv. Mellanaise) to 74.08 mg/g of GAE t (cv. Franquette). The antioxidant capacity of aqueous extracts was assessed through reducing power assay, scavenging effects on DPPH (2,2-diphenyl- 1-picrylhydrazyl) radicals and b-carotene linoleate model system. A concentration-dependent antioxidative capacity was verified in reducing power and DPPH assays, with EC50 values lower than 1 mg/ mL for all the tested extracts. The antimicrobial capacity was screened against Gram positive and Gram negative bacteria, and fungi. All the extracts inhibited the growth of Gram positive bacteria, being Staphylococcus aureus the most susceptible one with MIC of 0.1 mg/mL for all the extracts. The results obtained indicate that walnut green husks may become important in the obtainment of a noticeable source of compounds with health protective potential and antimicrobial activity.